1990
DOI: 10.1097/00000658-199004000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Wound Infection Rates After Invasive Procedures in HIV-1 Seropositive Versus HIV-1 Seronegative Hemophiliacs

Abstract: One-hundred and two patients with hemophilia A, hemophilia B, or acquired antibody to factor VIII who had undergone invasive procedures were cross referenced with patients participating in an ongoing prospective natural history study of HIV-1 infection in hemophiliacs. Matching revealed that HIV-1 status was known for 83 patients (83%) who had undergone 169 procedures between July 1979 and April 1988. Invasive procedures were classified as clean in 108 patients (63.9%), clean-contaminated in 45 (26.6%), contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 29 publications
0
23
0
2
Order By: Relevance
“…24 Evidence has shown that wound healing is not clinically impaired in patients with asymptomatic human immunodeficiency virus infection. 51,52 Wound healing in patients with acquired immune deficiency syndrome may be impaired but the cause is not definitively known. 24 Wound infections in these patients should be responsive to conventional therapy.…”
Section: Host Factorsmentioning
confidence: 99%
“…24 Evidence has shown that wound healing is not clinically impaired in patients with asymptomatic human immunodeficiency virus infection. 51,52 Wound healing in patients with acquired immune deficiency syndrome may be impaired but the cause is not definitively known. 24 Wound infections in these patients should be responsive to conventional therapy.…”
Section: Host Factorsmentioning
confidence: 99%
“…On the other hand, delayed diagnosis and late surgical exploration result in increased morbidity and mortality 5 . Although profound immunodeficiency is associated with poor prognosis, asymptomatic HIV-infected patients recover well from surgery and do not appear to suffer delayed healing 6,7 . Yet, with new antiviral therapy the operative mortality has dropped as much as necessary for emergency abdominal surgery and the riskbenefit analysis is now more in favour of laparotomy 5,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Information about early sepsis after implant surgery is becoming available [1,3,5,6,8,9,11,12], but evidence about late sepsis is required for appropriate decisionmaking. In the case of arthroplasty, the principal benefit may be lost if the implant is removed, whereas in the case of implants for fracture fixation or arthrodesis, removal after bony union has occurred is not detrimental.…”
Section: Introductionmentioning
confidence: 99%